Sex-specific neuromuscular and kinematic analysis of unanticipated single-leg landings in young athletes - Romanchuk, N. (School of Human Kinetics, Faculty of Health Sciences, University of Ottawa, 2019)
Despite the higher incidence of anterior cruciate ligament injuries in pediatric female populations, limited research has investigated sex-differences in youth biomechanics. Furthermore, research involving jump mechanics typically requires participant to follow a set protocol, such as sticking the landing. To reduce variability and improve reliability, trails where participants fail to meet the required protocol are discarded; however, significant clinical findings may be elucidated from these trials. The purpose of this thesis was to provide a complete biomechanical analysis of unanticipated single-leg drop-jump landings in youth athletes. Thirty-two healthy youth athletes completed unanticipated single-leg drop-jump landings on their dominant limb. Trials where participants shifted foot position or touched the ground with the contralateral leg were categorized as failed. Drop-jump landings were time-normalized using landmarks within the drop-jump task. Statistical parametric mapping (SPM) determined time-varying sex-differences in muscle onset time, co-activation, kinematics and kinetics. Wilcoxon signed-rank tests and paired sample t-tests compared lower-limb kinematics, centre-of-mass excursion and muscle activation amplitudes during the successful and failed landings. A logistic regression model was also fit to predict the likelihood of a successful landing. SPM identified significantly greater trunk flexion angle in males during the deceleration, flight, and landing phase of the drop-jump. Greater quadriceps-gastrocnemius co-activation was identified during the flight phase in female participants and independent sample t-test identified longer muscle onset time in the vastus lateralis of male participants. When comparing failed and successful landings greater hip abduction and less external rotation angles were observed during the successful trials. In addition, greater preparatory muscle activation was observed in the rectus femoris and semitendinosus during the flight phase of the failed landings. A logistic regression model, which included eight kinematic and neuromuscular variables, offered a training classification accuracy of 70% and a leave-one-out cross-validation accuracy of 65%. In conclusion, females land in a more erect posture and may be less effective at dissipating landing forces. In addition, greater co-activation and shorter pre-activations of the lower limb musculature may indicate a less effective muscle activation strategy in females. Furthermore, hip kinematics and the surrounding musculature play an important role in controlling successful and failed unanticipated landings. The variables included in the logistic regression model indicate which key factors are linked to landing a jump successfully. Training modalities aimed at improving landing mechanics should therefore focus on modifying these variables.